2005
DOI: 10.1007/s00421-005-0077-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the increase of effectiveness indexes and the increase of muscular efficiency with cycling power

Abstract: We determined the index of effectiveness (IE), as defined by the ratio of the tangential (effective force) to the total force applied on the pedals, using a new method proposed by Mornieux et al. (J Biomech, 2005), while simultaneously measuring the muscular efficiency during sub-maximal cycling tests of different intensities. This allowed us to verify whether part of the changes in muscular efficiency could be explained by a better orientation of the force applied on the pedals. Ten subjects were asked to per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 22 publications
4
71
2
2
Order By: Relevance
“…Values in handcycling are more comparable to those of cycling (Coyle et al, 1991), as differentiated from those of manual wheelchair propulsion, which might be explained by a closed loop movement. Also comparable to cycling (Zameziati et al, 2006) is that force application appears continuous throughout the propulsion cycle (Figure 4).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Values in handcycling are more comparable to those of cycling (Coyle et al, 1991), as differentiated from those of manual wheelchair propulsion, which might be explained by a closed loop movement. Also comparable to cycling (Zameziati et al, 2006) is that force application appears continuous throughout the propulsion cycle (Figure 4).…”
Section: Discussionmentioning
confidence: 68%
“…According to the literature on manual wheelchair propulsion or cycling (Boninger et al, 1997;Zameziati Figure 1 -Schematic setup. Kinematic marker (• anatomical, ο technical) positions are indicated on the left side and handgrip kinetics, on the right side.…”
Section: Kinetic Datamentioning
confidence: 99%
“…The studies include untrained up to elite and professional cyclists (including world top), different exercise protocols, and Zameziati et al (2006) various procedures to calculate metabolic rate and external power. However, all studies used respiratory exchange ratio values to convert oxygen uptake rate to metabolic rate.…”
Section: Cadence and Work Ratementioning
confidence: 99%
“…It has been shown that applying optimal oriented forces to the pedal during cycling enhances power output (PO) for comparable load magnitudes (Davis and Hull 1981). Furthermore, motive efficiency plays a determinant role in modulating muscular efficiency changes at a constant pedaling rate (Zameziati et al 2006).…”
Section: Introductionmentioning
confidence: 99%